The Influence of Ease of Use, Privacy, Security and Efficiency on Shopping Decisions Using the TikTok Shop - Riki Amelia Nasution; Yudi Prayoga; Abd. Halim (PT Mattawang Mediatama Solution, 2022)
Tiktok is a video-based social media, where users share videos with each other through their respective personal accounts. Tiktok is considered very entertaining and has a number of users that continue to increase every day. As users increase, and many users use the tiktok application to sell, tiktok adds the Tiktok shop feature to its application. This study wants to analyze the factors that influence consumer shopping decisions to make online purchases through the Tiktok Shop application. As we know, there are many other e-commerce applications that have existed for a long time and dominate the e-commerce market, such as Shopee, Lazada, Tokopedia and others. This is what causes interested researchers to raise this topic as research, because tiktok, which is a new social commerce, is able to compete with its predecessors which have long existed in Indonesia. This research is a quantitative research. Data is collected through a google form which is distributed via social media. This data collection technique was chosen because it can collect large amounts of data in a relatively short time and at minimal cost. The results of the study show that all independent variables have a positive and significant influence on consumers' shopping decisions using the tiktok shop application.